Role of sRNAs and a response regulator in response to oxidative stress in Rhodobacter sphaeroides - Peng, Tao; Justus Liebig University Giessen (My University, 2016)
A previous study showed that several sRNAs are induced by singlet oxygen in R. sphaeroides. The function of sRNAs CcsR1-4 and SorX were in the focus of this study. Overexpression of CcsR1-4 enhanced resistance to superoxide and organic hydroperoxides. Based on transcriptome analysis, several mRNAs of genes related to C1 metabolism or encoding components of the pyruvate dehydrogenase complex showed lower expression levels in CcsR1-4 overexpression strain. By using an in vivo lacZ based reporter system, the flhR mRNA was proven as a direct interaction partner of CcsR1-4. The flhR mRNA is known to encode a putative transcriptional activator of glutathione (GSH)-dependent methanol/formaldehyde metabolism (Hickman et al., 2004). Down-regulation of flhR mRNA represses the glutathione-dependent pathway, which increases the pool of glutathione. More glutathione would be used to counteract oxidative stress. The FlhR-dependent down-regulation of C1 metabolism reduces the main source of reactive oxygen species.SorX is derived from the 3´ UTR of the ompR mRNA which encodes a response regulator. Deletion of sorX caused a higher sensitivity to singlet oxygen and organic hydroperoxides. The 75 nt SorX is generated from the 3´ UTR of the ompR transcript by RNase E cleavage and considerably conserved among related species. The 75-nt SorX is sufficient for enhancing resistance to singlet oxygen and organic hydroperoxides. The sRNAs CcsR1-4 and SorY which have a reported role in the oxidative stress response are affected by SorX. A potA mRNA encoding a subunit of a polyamine transporter was identified as a direct target of SorX. Deletion of potA increased resistance to singlet oxygen and organic hydroperoxides. Moreover, SorX enhances resistance by targeting potA. The PotABCD transporter can specifically uptake spermidine in E. coli (Kashiwagi et al., 1993). High spermidine level significantly increases ROS level and causes increased sensitivity of R. sphaeroides to organic hydroperoxides. It was assumed that less uptake of spermidine counteracts oxidative stress, due to down-regulation of potA by SorX in R. sphaeroides.Besides sRNAs induced by singlet oxygen, some proteins were also identified by proteome analysis including a response regulator OmpR homologous protein. Western blot and real time RT-PCR showed that various stress conditions can induce OmpR protein levels and ompR expression. Overexpression of a flag-tagged OmpR enhanced resistance to organic hydroperoxides. The flag-tagged OmpR protein is able to up-regulate promoter activity of RSP_6037 which encods a hypothetical protein and the mRNA level of RSP_6037, however, the OmpR protein down-regulates the promoter activity of rpoHI and its mRNA level. These data confirmed that RSP_6037 and rpoHI are regulated by OmpR. Furthermore, CcsR1, which is transcribed with the upstream gene RSP_6037, was also accumulated by overexpression of the flag-tagged OmpR protein.
Keywords: ddc:570